Use of Satellite Technology for Forest Cover Area Monitoring in a Blockchain-Based Carbon Trading Scheme - Haryono, Haryono (Westscience Press, 2025)
This study explores the utilization of satellite technology, Geographic Information Systems (GIS), and blockchain to enhance forest cover monitoring and enable a transparent carbon trading mechanism. Satellite high-resolution imagery and GIS analysis were applied in estimating forest cover change and carbon sequestration potential. In addition, a blockchain prototype was also developed to automatically issue and exchange carbon credits using smart contracts to ensure transparency and efficiency. Findings indicate a 7.5% reduction in forest cover in the study area over five years, with the highest deforestation hotspots discovered through spatial analysis. The blockchain platform was successful in automating carbon credit transactions with an average processing time of 15 seconds and ensuring secure and immutable records. Stakeholder feedback highlighted the capacity of the system to simplify regulatory oversight and promote trust in carbon marketplaces. The study points to the feasibility and scalability of integrating such technologies to address deforestation, enhance carbon trading mechanisms, and aid global sustainability goals.